Transformers. - Kruger, Ehren, 1972-; McDormand, Frances; Malkovich, John; Turturro, John, 1957- (2011)
The Autobots learn of a Cybertronian spacecraft hidden on the moon and race against the Decepticons to reach it and to learn its secrets.